Effects of alternative cropping systems on globe artichoke qualitative traits. (28th August 2017) - Spanu, Emanuela; Deligios, Paola A; Azara, Emanuela; Delogu, Giovanna; Ledda, Luigi
Abstract: BACKGROUND: Traditionally, globe artichoke cultivation in the Mediterranean basin is based on monoculture and on use of high amounts of nitrogen fertiliser. This raises issues regarding its compatibility with sustainable agriculture. We studied the effect of one typical conventional (CONV) and two alternative cropping systems [globe artichoke in sequence with French bean (NCV1), or in biannual rotation (NCV2) with cauliflower and with a leguminous cover crop in inter‐row spaces] on yield, polyphenol and mineral content of globe artichoke heads over two consecutive growing seasons. RESULTS: NCV2 showed statistical differences in terms of fresh product yield with respect to the monoculture systems. In addition, the dihydroxycinnamic acids and dicaffeoylquinic acids of non‐conventional samples were one‐fold significantly higher than the conventional one. All the samples reported good mineral content, although NCV2 achieved a higher Fe content than conventional throughout the two seasons. After two and three dates of sampling, the CONV samples showed the highest levels of K content. CONCLUSION: In our study, an acceptable commercial yield and quality of 'Spinoso sardo' were achieved by shifting the common conventional agronomic management to more sustainable ones, by means of an accurate choice of cover crop species and rotations introduced in the systems. © 2017 Society of Chemical Industry